The Green and Efficient One-pot Synthesis of Tetrahydrobenzo[b]pyran Derivatives - Ankush, Bhaskar P.; Shitole, Balasaheb V.; Shitole, Nana V. (Orbital: The Electronic Journal of Chemistry, 2023)
Glutamic acid is used as an efficient organocatalyst for one-pot synthesis of tetrahydrobenzo [b]pyran via condensation of an aromatic aldehyde, dimedone and malononitrile in ethanol: water (1:4) as solvent at reflux temperature. The short reaction time, cleaner reaction, and easy workup make this protocol practical and economically attractive.